2006
DOI: 10.1097/01.sla.0000217592.04061.d5
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain After Short- and Long-Limb Gastric Bypass in Patients Followed for Longer Than 10 Years

Abstract: The gastric bypass limb length does not impact long-term weight loss. Significant weight gain occurs continuously in patients after reaching the nadir weight following gastric bypass. Despite this weight gain, the long-term mortality remains low at 3.1%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
343
4
19

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 646 publications
(389 citation statements)
references
References 9 publications
19
343
4
19
Order By: Relevance
“…One of the limitations of the present study was the short follow-up of 50 days. However, this period is equivalent to 3 human years [19]. Although we could not exclude the potential for weight regain after SG, other investigators have demonstrated that weight loss is maintained at 15 weeks after SG in rodents [20,21].…”
Section: Discussionmentioning
confidence: 92%
“…One of the limitations of the present study was the short follow-up of 50 days. However, this period is equivalent to 3 human years [19]. Although we could not exclude the potential for weight regain after SG, other investigators have demonstrated that weight loss is maintained at 15 weeks after SG in rodents [20,21].…”
Section: Discussionmentioning
confidence: 92%
“…6 In fact, patients with a lower postoperative gut hormone response were demonstrated to achieve a lower BW loss after gastric bypass compared with patients with a more potent postprandial response of PYY and GLP-1. 6 Patients with poor BW loss or significant BW regain after surgery 28,29 are currently left with limited therapeutic options. Surgical revision, including reduction of pouch size or lengthening of the Roux limb, 30 is frequently used despite the lack of supporting evidence in the literature.…”
Section: Time [H] Food Intake [G]mentioning
confidence: 99%
“…Even though earlier findings report that patients are satisfied with weight loss and quality of life after weight loss surgery, a substantial number of patients fail to achieve weight loss, regain weight or experience challenges in close relationships (Christou, Look, & Maclean, 2006; Groven, Råheim, & Engelsrud, 2013; Lier et al, 2016; ; SOReg, 2014). There is a need for further research on the identification of family factors that are important in maintaining lifestyle changes and the stability and wellbeing of the family after weight loss surgery.…”
Section: Discussionmentioning
confidence: 99%